PELESTARIAN VOKAL TEMBANG BALI DENGAN MEDIA RADIO PANCAR ULANG DI ERA COVID-19 - I Ketut Muada; I Wayan Sugama (Widyadari : Jurnal Pendidikan, 2020)
Tembang has an impantant role in the life of Hindu people in Bali. Learning tembang as well as learning the language, script, metrum, cutural cancepts and values which is cantained in the literature.Tembang means”nembang” (sing) associated with the word “kembang” wich means plower (sekar in balinese). Plawer have a role and function as a sourse of beauty where the good Kama (god of beauty) stay over in reality. Generating lust in line with the function and the role of flawers or gods Kama at the ceremonies that take place in Bali. The emergence of seka pesantian or group of people in pursuing tembang in Bali nowadays, in a huge appreciation for balinese people in preserving the vokal of Balinese tembang the “pesantian”or the Balinese tembang association had never stopped looking for ways to lee ableto perform Balinese tembang in the community. Although in the presence of Covid-19 era people are adirsed not to gather (not dount) to cut of the spread of the Covid-19 virus. For the “sekaa pesantian” it did not dampen their interest in preserving Balinese song vocals (tembang) one of the ways in using radio transmiting media ((amatir radio) as a start up to carreg in Balinese tembang from home or interacting remotely.